Pengaruh Efektivitas Penerimaan Pajak Bumi dan Bangunan terhadap Pendapatan Asli Daerah di Badan Pendapatan Daerah Kabupaten Gorontalo - Yusuf, Fitria Melynsyah (JSAP : Journal Syariah and Accounting Public, 2023)
Land and building tax has a wider impact because the proceeds from Land and Building Tax are returned to increase regional development income. The aim of this research is to determine the effectiveness of land and building tax revenue on local revenue in the Gorontalo Regency Regional Revenue Agency. This research method is quantitative descriptive research. The quantitative analysis used is simple linear regression analysis. The results of the research show that in the regression it is known that the land and building tax revenue variable has a t value of -.135 and a sig of 0.901. So it means that the tcount is smaller than the T table (-.135 > 3.182), and the significant value is greater than 0.05 (0.901 < 0.05), then HO is rejected and H1 is accepted. So it is concluded that land and building tax revenues do not have a significant influence on local income in Gorontalo Regency in 2018-2022.